The Influence of the Team Games Tournament (TGT) Learning Model Assisted by Wordwall on the Scientific Literacy of Class V Elementary School Students - Adila Luthfi Saputri; Wati Sukmawati (Jurnal Penelitian Pendidikan IPA, 2024)
This study aims to present the results of a study that compares the effectiveness of two learning methods, namely the Team Games Tournament (TGT) assisted by Wordwall and conventional learning methods, in improving the science literacy skills of grade V elementary school students. The research method uses a quasi-experimental method by using an experimental class applying TGT assisted by Wordwall, while the control class uses conventional learning methods. Data obtained from both groups of students were analyzed to evaluate the improvement of science literacy skills. The results showed that the experimental class experienced a significant improvement in science literacy skills compared to the control class. Wordwall-assisted TGT approach creates a more interactive, collaborative, and engaging learning environment for students, which encourages active participation and increases their motivation to learn. On the other hand, conventional methods show some students experiencing a decline in ability, highlighting the need for a more varied and interactive approach to learning. These results underscore the importance of innovation in learning methods to improve the quality of science education in primary schools, with great potential to apply the Wordwall-assisted TGT model widely in this context.